G-Protein Coupled Receptor Targeting on Myeloid Cells in Atherosclerosis - van der Vorst, Emiel P. C.; Peters, Linsey J. F.; Müller, Madeleine; Gencer, Selin; Yan, Yi; Weber, Christian; Döring, Yvonne (Frontiers in Pharmacology, 2019)
Atherosclerosis, the underlying cause of the majority of cardiovascular diseases (CVD), is a lipid-driven, inflammatory disease of the large arteries. Gold standard therapy with statins and the more recently developed proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have improved health conditions among CVD patients by lowering low density lipoprotein (LDL) cholesterol. Nevertheless, a substantial part of these patients is still suffering and it seems that ‘just’ lipid lowering is insufficient. The results of the Canakinumab Anti-inflammatory Thrombosis Outcome Study (CANTOS) have now proven that inflammation is a key driver of atherosclerosis and that targeting inflammation improves CVD outcomes. Therefore, the identification of novel drug targets and development of novel therapeutics that block atherosclerosis-specific inflammatory pathways have to be promoted. The inflammatory processes in atherosclerosis are facilitated by a network of immune cells and their subsequent responses. Cell networking is orchestrated by various (inflammatory) mediators which interact, bind and induce signaling. Over the last years, G protein coupled receptors (GPCRs) emerged as important players in recognizing these mediators, because of their diverse functions in steady state but also and specifically during chronic inflammatory processes - such as atherosclerosis. In this review, we will therefore highlight a selection of these receptors or receptor sub-families mainly expressed on myeloid cells and their role in atherosclerosis. More specifically, we will focus on chemokine receptors, both classical and atypical, formyl-peptide receptors, the chemerin receptor 23 and the calcium-sensing receptor.We will, if possible, also detail on consequences of their targeting which may hold promising options for future treatment of CVD.